Use of genetic models of idiopathic hypogonadotrophic hypogonadism in mice and men to understand the mechanisms of disease. Issue 11 (21st October 2013) - Lippincott, Margaret F.; True, Cadence; Seminara, Stephanie B.
New findings What is the topic of this review? This review discusses the genetics of idiopathic hypogonadotrophic hypogonadism, with a focus on how deficiencies in the kisspeptin and neurokinin B pathways result in reproductive dysfunction in both mice and men. What advances does it highlight? In humans, deficiencies in kisspeptin signalling lead to a sustained absence of puberty. Mutations in the neurokinin B pathway are also associated with an initial absence of pubertal development, but the hypogonadotrophism can improve later in life with spontaneous activation of the hypothalamic–pituitary–gonadal cascade. Mouse models with mutations in each of these pathways recapitulate many of the features observed in human patients. Spontaneous recovery of gonadotrophin‐releasing hormone secretion, termed 'reversal', indicates that the hypothalamic–pituitary–gonadal axis may be capable of awakening in the setting of neurokinin B signalling abnormalities. Mutations in the genes encoding the neuropeptides kisspeptin and neurokinin B, as well as their receptors, are associated with gonadotrophin‐releasing hormone (GnRH) deficiency and a failure to initiate and/or progress through puberty. Although the total number of patients studied to date is small, mutations in the kisspeptin pathway appear to result in lifelong GnRH deficiency. Mice with mutations in kisspeptin and the kisspeptin receptor, Kiss1−/− and Kiss1r−/−, respectively, appear to be phenocopies of the human with abnormal sexual maturation and infertility. In contrast, mutations in the neurokinin B pathway lead to a more variable adult reproductive phenotype, with a subset of hypogonadotrophic individuals demonstrating paradoxical recovery of reproductive function later in life. While 'reversal' remains poorly understood, the ability to recover reproductive function indicates that neurokinin B may play different roles in the initiation of sexual maturation compared with the maintenance of adult reproductive function. Mice with mutations in the gene encoding the neurokinin B receptor, Tacr3, have abnormal oestrous cycles and subfertility but, similar to their human counterparts, appear less severely affected than mice with kisspeptin deficiency. Further investigations into the interaction between the kisspeptin and neurokinin B pathways will reveal key insights into how GnRH neuronal modulation occurs at puberty and throughout reproductive life.